LREE-enriched mafic gneiss and meta-ultramafic rock from Tonagh Island in the Napier Complex, East Antarctica - Owada,Masaaki; Osanai,Yasuhito; Tsunogae,Toshiaki; Toyoshima,Tsuyoshi; Hokada, Tomokazu; Crowe,Warwick A. (National Institute of Polar Research, 2000)
P(論文) Mafic gneisses and meta-ultramafic rocks are exposed on Tonagh Island These rocks are high-Mg composition and have undergone ultrahigh-temperature metamorphism Most of the mafic gneisses and the meta-ultramafic rocks occur as intercalated layers or lenses within the quartzo-feldspathic gneisses Some of the mafic gneisses and the meta-ultramafic rocks locally cut the layers or foliations of neighboring quartzo-feldspathic gneisses, suggesting that these mafic gneisses and meta-ultramafic rocks were originally intrusive rocks Major and trace element compositions of the mafic gneisses and the meta-ultramafic rocks resemble those of komatiitic basalt to komatiite from the Archaean greenstone belt Light REE-enriched and flat patterns are recognized in the mafic gneisses and meta-ultramafic rocks although the REE pattern of the deformed sample is convex upward In the Mt Riiser-Larsen region situated 40 km northeast from Tonagh Island, it has been found in a previous study that the LREE-enriched mafic gneisses and meta-ultramafic rocks have been derived from komatiitic rocks whose chemical trends show magmatic variations Therefore, the LREE-enriched patterns of mafic gneisses and ultramafic rocks on Tonagh Island and in the Mt Riiser-Larsen region could be inherited from the chemical nature of original rocks prior to undergoing ultrahigh-temperature metamorphism The LREE-enriched pattern cannot be explained by interaction between an LREE-flat parental magma and an LREE-enriched crustal material m terms of geochemical constraints Hence, the LREE-enriched and flat types of the mafic gneisses and the meta-ultramafic rocks on Tonagh Island would have been derived from different source mantles with respect to LREE signatures departmental bulletin paper